PENGARUH STRENGTHENING EXERCISE TERHADAP PENURUNAN INTENSITAS NYERI LUTUT PADA PENDERITA OSTEOARTHRITIS - icca narayani Pramudaningsih; wahyu sarayosa rahmawati devi (Jurnal Profesi Keperawatan, 2017)
Abstract Knee osteoarthritis (OA) is a chronic knee joint disorder with knee joint damage, in the form of disintegration and bony edge growth (osteophytes) that cause pain in the knee. One of the non-pharmacological therapy that can reduce the intensity of pain is to do Strengthening Exercise The purpose of this study was to determine the effect of Strengthening Exercise in decreased knee pain intensity in Osteoarthritis patients This case study design is Quesy experiment using a control group design pre-post-test with a total sample of 46 people using total sampling technique, 23 intervention samples and 23 control samples. The results of this study were knee pain in the control group before and after without strengthening exercise average respondents experienced moderate knee pain as much as 17 people (73.9%) and Pain knee respondents in the intervention group before doing Strengthening Exercise average respondents had knee pain while as many as 17 people (73.9%) and after strengthening exercise the average respondents experienced mild joint pain as much as 16 people (69.6%). Based on the research, it can be concluded that there is a difference of knee pain in the intervention group with p value of 0.000 and the difference of knee pain in the control group with p value of 0.011 Keywords: Knee osteoarthritis, knee pain, strengthening exercise.  Intisari             Osteoarthritis (OA) lutut adalah gangguan sendi lutut yang bersifat kronis disertai kerusakan tulang sendi lutut, berupa disintegrasi dan pertumbuhan tepi tulang (osteofit) yang menyebabkan nyeri pada lutut. Salah satu terapi non farmakologi yang dapat menurunkan intensitas nyeri adalah dengan melakukan Strengthening Exercise Tujuan penelitian ini adalah untuk mengetahui pengaruh Strengthening Exercise dalam penurunan intensitas nyeri lutut pada penderita Osteoarthritis Rancangan studi kasus ini adalah Quesy eksperimen dengan menggunakan bentuk rancangan control group pre test-post test dengan jumlah sampel sebanyak 46 orang dengan menggunakan teknik total sampling, 23 sampel intervensi dan 23 sampel kontrol. Hasil dari penelitian ini adalah Nyeri lutut pada kelompok kontrol sebelum dan sesudah tanpa melakukan strengthening exercise rata-rata responden mengalami nyeri lutut sedang sebanyak 17 orang (73.9%) dan Nyeri lutut responden pada kelompok intervensi sebelum melakukan Strengthening Exercise rata-rata responden mengalami nyeri lutut sedang sebanyak 17 orang (73.9%) dan sesudah melakukan strengthening exercise rata-rata responden mengalami nyeri sendi ringan sebanyak 16 orang (69.6%). Berdasarkan penelitian tersebut maka diperoleh kesimpulan bahwa Adanya perbedaan nyeri lutut pada kelompok intervensi dengan nilai p value sebesar 0.000 dan adanya perbedaan nyeri lutut pada kelompok kontrol dengan p value sebesar 0.011 Kata kunci : Osteoarthritis lutut, Nyeri lutut, strengthening exercise.